Comparative molecular subtyping of Salmonella enterica serovar typhi by VNTR, rep-PCR and restricted AP-PCR / Sepideh Rezanejad Shirazi - Shirazi, Sepideh Rezanejad (2009)
In this study, Salmonella enterica serovar Typhi (S. Typhi) strains collected from outbreak and sporadic cases of typhoid fever during the years 1998 to 2007 in Malaysia were characterized using three PCR-based methods, i.e., restricted arbitrarily primed PCR (resAP-PCR), repetitive element PCR (rep-PCR) and variable-number tandem repeat (VNTR) analysis. The objective of this study was to explore the utility of VNTR and resAP-PCR as newer molecular methods in comparison with the commonly used method of rep-PCR to subtype S. Typhi. ResAP-PCR analysis was conducted using arbitrary primers STHae8 and STAlu9 following endonuclease digestion of S. Typhi DNA with HaeIII and AluI enzymes. Rep-PCR was performed by using REP-F and REP-R primers, corresponding to the highly conserved REP repeated DNA elements. VNTR analysis was performed by multiplex approach using four primers (TR1, TR2, TR3, TR5) flanking VNTR loci in the CT18 strain of S. Typhi. The S. Typhi strains were typeable by three methods in assigning a defined type to each strain tested. Restricted AP-PCR amplification of HaeIII and AluI digested DNA using STHae8 and STAlu9 primers was not able to discriminate S. Typhi strains tested. In addition, resAP-PCR analysis using STHae8 primer demonstrated poor reproducibility. Similarly, rep-PCR with the primers REP-F and REP-R was not useful as a subtyping tool for S. Typhi as all strains shared the same predominant banding profile. In contrast, multiplex VNTR assay displayed diversity based on four VNTR loci studied, with total allele numbers ranging from 2 to 19 and Nei’s diversity (D) values ranging from 0.04 to 0.93. Sequence analysis of individual alleles confirmed the presence of VNTRs among the strains and identified 42 VNTR profiles. The results revealed that the copy number of repeats in CT18 strain of S.Typhi was highly correlated with the D value (R2 = 0.57) and number of alleles (R2 =0.87) observed across diverse strains. The VNTR analysis showed that significant genetic heterogeneity exists at TR1, TR2 and TR3 loci of S. Typhi strains in Malaysia. Analysis of the VNTR patterns indicated that S. Typhi strains obtained from sporadic cases were much more heterogeneous than those obtained during outbreaks of typhoid fever. The findings in this study demonstrate that VNTR is able to provide a rapid, highly discriminative, and reproducible typing method for epidemiological surveillance and outbreak investigation of S. Typhi strains.